Jazz fest : a New Orleans story [videorecording (DVD)] (Sony Pictures Home Entertainment, 2022)
The New Orleans Jazz & Heritage Festival presented by Shell, aka "Jazz Fest," is the signature annual music and cultural event of the city and has been called America's greatest festival. Celebrating the music, food, and arts and crafts of all of Louisiana since 1970, Jazz Fest is an essential showcase of the rich heritage of the region, and hundreds of thousands attend the event each year. Local music heroes are joined on fourteen stages by some of the most prominent figures in entertainment, highlighting the connections between Louisiana culture and the world. This documentary weaves together live performances and interviews from the 50th anniversary of the iconic festival, featuring some of the biggest names in the music industry. This film not only captures the Festival in all of its beauty and glory, but also delves deep into the rich culture of The Big Easy.